Diet shapes cold‐water corals bacterial communities. (1st December 2019) - Galand, Pierre E.; Remize, Marine; Meistertzheim, Anne‐Leila; Pruski, Audrey M.; Peru, Erwan; Suhrhoff, Tim Jesper; Le Bris, Nadine; Vétion, Gilles; Lartaud, Franck
Summary: Different cold‐water coral (CWC) species harbour distinct microbial communities and the community composition is thought to be linked to the ecological strategies of the host. Here we test whether diet shapes the composition of bacterial communities associated with CWC. We compared the microbiomes of two common CWC species in aquaria, Lophelia pertusa and Madrepora oculata, when they were either starved, or fed respectively with a carnivorous diet, two different herbivorous diets, or a mix of the 3. We targeted both the standing stock (16S rDNA) and the active fraction (16S rRNA) of the bacterial communities and showed that in both species, the corals' microbiome was specific to the given diet. A part of the microbiome remained, however, species‐specific, which indicates that the microbiome's plasticity is framed by the identity of the host. In addition, the storage lipid content of the coral tissue showed that different diets had different effects on the corals' metabolisms. The combined results suggest that L . pertusa may be preying preferentially on zooplankton while M . oculata may in addition use phytoplankton and detritus. The results cast a new light on coral microbiomes as they indicate that a portion of the CWC's bacterial community could represent a food influenced microbiome.